An improved polymerase chain reaction assay for the detection of Tritrichomonas foetus in cattle - Nickel, D. Douglas (2002)
An improved polymerase chain reaction test has been developed to detect Tritrichomonas foetus, the causative agent of trichomoniasis in cattle. The test amplifies a region of the 5.8S ribosomal RNA gene of T. foetus, and it is simple, sensitive, and specific when compared with traditional methods to examine field samples.